マクマードキチ アムンゼン・スコット ナンキョクテンキチ オヨビ スコットキチ ノ セツエイ カツドウ - 石沢, 賢二; イシザワ, ケンジ; Ishizawa, Kenji (1998)
P(論文) 平成9年度交換科学者として, 1997年12月初めから約2週間, 米国マクマード基地, アムンゼン・スコット南極点基地およびニュージーランドのスコット基地を訪れ, 輸送形態, 設営施設, 廃棄物処理方法などを調査した。米国基地では, 観測と設営の区分はもとより, 詳細な業務に至るまで完全に分業化がなされているのに驚かされた。また, 各基地とも航空機を活用し, 夏期間に活発な活動を行っているのが印象的だった。さらに, 廃棄物処理では, 排水や可燃物処理において日本隊の方法と大きな違いがあった。南極に特有な自然をうまく利用した氷の井戸を使った造水や太陽光を利用した暖房, 風力発電機などの設備は注目に値した。 In December of 1997 the author visited the U.S. McMurdo and Amundsen-Scott South Pole Stations and New Zealand Scott Base as an Exchange Scientist. The author's investigation was focused on the transportation system, facilities and waste management. The author was surprised to see a working system at the U.S. stations that involved complete division of labor. In addition, he was impressed that they made good use of aircraft and did efficient work in the summer season. There were great differences between Japan and U.S. in management of combustible waste and sewage disposal. The utilization of native characteristics of Antarctica such as water wells, passive solar energy and wind turbines is worthy of note. departmental bulletin paper